Produk-Produk Jasa Pendidikan - Bambang Wiyono (Intizam, Jurnal Manajemen Pendidikan Islam, 2020)
Educational services products have a very important role in improving education quality. With quality educational service products, of course, it will also produce high quality education as well. To realize this, a creative management strategy for educational service products is needed. This article intends to describe the definition, characteristics and form of educational services products. In addition, this article also discusses the strategy of educational service products to develop the quality of education by taking SD Baturaden as the case study setting. Educational services is an act or activity that does not exist, which contains the process of guiding children to achieve maturity of reason and action in interaction with the environment, which is carried out in meeting the needs of consumers. Educational services have the characteristics of lacking standards and uniformity (less standardized and uniform), production and consumption at the same time (simultananeous production and consumption), and are more intangible than intangible (more intangible thantangible). Forms of educational service products can be grouped into 3 types, namely (1) Reputation which is the ability of an educational institution's output consisting of abilities in the cognitive, psychomotor and attitude fields. (2) Prospect, which is the level of sustainability of the output of the educational institution after leaving the educational institution. (3) Variance, namely the availability of variations or various choices of various fields